LITERATURE STUDY: BLENDED LEARNING AS A POST-PANDEMIC NEW NORMAL LEARNING MODEL - Umus Sofia (maktab: Jurnal Pendidikan dan Teknologi, 2022)
The blended learning model is a model that combines a face-to-face learning system and an online learning system. This model is considered applicable in learning in the new normal. The purpose of this study is to examine more deeply about the blended learning model. The method used is a literature study method with qualitative data analysis techniques. The results of the literature study show that the blended learning model is very suitable to be applied to the new normal era education system. This model is useful not only to increase students' understanding but also to develop their skills in using technology and train students' independence in learning. In addition, there are other advantages, such as developing pedagogics from what was originally traditional to modern pedagogics, increasing access and flexibility, and increasing the effectiveness of education costs.